2012
DOI: 10.1074/jbc.m111.316232
|View full text |Cite
|
Sign up to set email alerts
|

Human High Temperature Requirement Serine Protease A1 (HTRA1) Degrades Tau Protein Aggregates

Abstract: Background: Protein quality control proteases degrade damaged proteins and protein fragments. Results:The human serine protease HTRA1 degrades tau aggregates and is induced by its substrates. Conclusion: A member of the widely conserved HtrA family is involved in protein quality control in mammalian cells. Significance: HTRA1 might function as a tau protease in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
87
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 62 publications
2
87
0
Order By: Relevance
“…Furthermore, HtrA1 colocalizes with amyloid deposits in human brain samples [36]. HtrA1 also degrades aggregated and fibrillar tau protein; neuronal cells and patient brains accumulate less tau, neurofibrillary tangles, and neuritic plaques, respectively, when HtrA1 is expressed at elevated levels [43,44]. These data suggest that HtrA1 performs regulated proteolysis during protein quality control which protects the brain against accumulation of amyloid deposits and tau neurofibrillary tangles e the hallmarks of the Alzheimer's disorder.…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 85%
“…Furthermore, HtrA1 colocalizes with amyloid deposits in human brain samples [36]. HtrA1 also degrades aggregated and fibrillar tau protein; neuronal cells and patient brains accumulate less tau, neurofibrillary tangles, and neuritic plaques, respectively, when HtrA1 is expressed at elevated levels [43,44]. These data suggest that HtrA1 performs regulated proteolysis during protein quality control which protects the brain against accumulation of amyloid deposits and tau neurofibrillary tangles e the hallmarks of the Alzheimer's disorder.…”
Section: Human Htra Proteins In Cellular Physiology and Pathogenesismentioning
confidence: 85%
“…This function of IGF-1 supports the concept that HtrA1 function may protect from an age-related disease (45,76) such as NvAMD. In addition to NvAMD, HtrA1 has been implicated in other age-related disorders like arthritis (36,46) and Alzheimer's disease (45,77). HtrA1 expression increases with age (78).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HtrA1 cleaves tau and the amyloid precursor protein (APP) (76)(77)(78), which is predicted to promote protection in the AD context. Furthermore, HtrA1 levels and activity are increased in response to the development of AD pathology (77).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that HtrA1 cleaves tau and the amyloid precursor protein (APP) (76)(77)(78), which is predicted to promote protection in the AD context. Furthermore, HtrA1 levels and activity are increased in response to the development of AD pathology (77). It was also recently established that HtrA1 degrades apoE4 more rapidly than apoE3 (22), which may contribute to the overall reduced levels of apoE4 detected in AD brain tissues as compared to apoE3.…”
Section: Discussionmentioning
confidence: 99%